2020
DOI: 10.1136/bmjopen-2019-031580
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Chinese version of the Person-Centred Care Assessment Tool

Abstract: ObjectiveThis study aims to test a Chinese cross-cultural adaptation of the English version of the Person-Centred Care Assessment Tool (P-CAT) and evaluate its psychometric properties.DesignP-CAT was translated/back-translated using established procedures before the psychometric evaluation of the Chinese version was made.SettingTwo hospitals covering urban and suburban areas of Kunming in the Yunnan province of China.Participants152 female hospital staff completed the survey.Main outcome measure(s)Construct va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…It was observed that 12 studies (48%) obtained α coefficients with greater distance from the central tendency (e.g., Zhong and Lou, 2013 ; Bökberg et al, 2019 ; Le et al, 2020 ). On the other hand, the studies with less weight, and consequently with a greater variation due to the size of their samples, tended to be located below the meta-analytic alpha value, suggesting a possible restriction of the variance that commonly occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that 12 studies (48%) obtained α coefficients with greater distance from the central tendency (e.g., Zhong and Lou, 2013 ; Bökberg et al, 2019 ; Le et al, 2020 ). On the other hand, the studies with less weight, and consequently with a greater variation due to the size of their samples, tended to be located below the meta-analytic alpha value, suggesting a possible restriction of the variance that commonly occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, and closely linked to the above, the P-CAT was created as a multidimensional measure, but the predominant use of the total score implies that users worked with the assumption of unidimensionality. Indeed, in about 13 substantive studies reviewed here, the total score was preferred over the individual dimension scores identified (e.g., Rokstad et al, 2012 ; Tak et al, 2015 ; Le et al, 2020 ). Also, Martínez et al ( 2015 ) found that the multidimensional and unidimensional model were indistinguishable in their SEM fit indices, additionally with interfactor correlations >0.90.…”
Section: Discussionmentioning
confidence: 99%
“…A review of this type is critical given some methodological issues that seem not to have been resolved in the P-CAT; for example, although the multidimensionality of the P-CAT was identi ed in the study that constructed it, Bru-Luna et al [22] recently stated that in adaptations of the P-CAT [16][17][18][19][20]25], the total score was used for interpretation, and multidimensionality was disregarded. Thus, the multidimensionality of the original study was apparently not replicated.…”
Section: Current Studymentioning
confidence: 99%
“…Our research team has a long record of research collaboration between the two countries [ 12 15 ], and during this collaboration we have found that there is a lack of research comparing the different healthcare systems regarding PC. Such comparison, though, is of importance for staff competence and the provision of evidence-based care in these multicultural countries.…”
Section: Introductionmentioning
confidence: 99%
“…International collaboration may seem to be essential to enable healthcare professionals to better respond to cultural diversity in evidence-based practice [ 28 ]. The previous sparse research and the research group’s longstanding collaboration in practice and research [ 12 15 ] is the background to mapping the knowledge of PC for older people in China and Sweden. Therefore, the aim of this systematic scoping review was to identify the characteristics of the body of literature and to examine the knowledge gaps concerning PC research for older people (> 60 years) in two healthcare systems and cultures, mainland China and Sweden.…”
Section: Introductionmentioning
confidence: 99%